W stroną mowy pozornie niezależnej, czyli o dialogu w polskiej prozie współczesnej - Mizerkiewicz, Tomasz (Wydawnictwo Naukowe UAM, 2004)
Dialogue as a part of Polish prose didn't attract enough attention. Its form changed along with literary conventions, for instance - realistic novels imitated common conversations. Nowadays Polish novelists use dialogues rather incidentally and often stress its unauthenticity. The speach of character is always quotation of phrases heard before. The new form of dialogue can be traced in Polish prose - some sentences seem to be given as direct speach, but close examination of their construction reveals their inderict essence. It should be called „reported direct speach" (as negative of „free indirect speach"). This form of dialogue is part of an important process descibed by contemporary philosophers as triumph of culture of writing over traditional culture of voice.
Towards reported direct speech (dialogue in the Polish contemporary prose)